INCREASE OF EFFICIENCY OF SUPPRESSION OF THE ACTIVE NOISE JAMMING IN RADAR INTERCEPTION OF AIR TARGETS IN THE REVIEW MODE - V. E. Markevich (Системный анализ и прикладная информатика, 2017)
The modified algorithm of the adaptive compensating of the active noise jamming, based on usage of the recurrence estimation of inverse covariance matrix of jamming in the course of an self-tuning is considered. The matrix estimation is formed by a method of a serial regression (SRM), a consequence application of a lemma about inversing of a matrix to differential – to the difference equation for a rounded estimation of direct covariance matrix of jamming (CMJ). The single estimation of straight line CMJ is formed as result dyad products of the instant vectors of noises in handling channels. In partial channels the adaptive transversal filters with the self-tuning on value of a signal of an aggregate error are implemented.In article skeleton diagrams of devices of the compensating implemented by various methods are resulted. Mathematical modeling of operation of the algorithms, implemented by a method of the least squares (criterion of a minimum RMS error) and a method of a serial regression is performed.Results of mathematical modeling of operation of the device of compensating of active noises jamming in the conditions of the active radio-electronic counteraction at multipath propagation of signals both non-identical amplitude and phase characteristics of channels of handling are resulted. Optimal values of technical parameters of devices of compensating of the active noises jamming providing obtaining of demanded values of coefficient of suppression are given. The comparative analysis of indexes of efficiency of classical and offered algorithms of compensating is made. Advantage of algorithm of compensating of the active noises jamming, using the recurrence estimation of a inverse covariance matrix of jamming is shown.The algorithm of functioning on the basis of SRM allows to lower essentially requirements to specialized VLSI (FPGA) at implementation is hardware – program complexes for preprocessing of the radar, radio communication and radio – navigation information in the conditions of influence of the active noises jamming in the presence of effects of multipath propagation of signals, in the presence of delay of signals on an antenna system aperture, and also at unremovable technological dispersion amplitude and phase characteristics of the microwave of channels of handling.